Effects of fermentation medium on cigar filler - Wen, Cai; Wanrong, Hu; Pinhe, Li; Jie, Liu; Qianying, Zhang; Quanwei, Zhou; Cheng, Luo; Dongliang, Li (Frontiers in Bioengineering and Biotechnology, 2022)
The addition of medium during industrial fermentation can improve the quality of cigar tobacco leaves after agricultural fermentation. In this study, the cigar filler tobacco "Brazilian Frogstrips YA14" was used as the test material to determine the contents of main chemical components in cigar tobacco leaves after fermentations with the additions of water (control group) and a medium (test group), and the changes in the community structure and abundances of bacteria on tobacco leaves during the fermentation process were analyzed. The results of the study were as follows: 1) During the fermentation process, the protein content of tobacco leaves fluctuated slightly, basically stabilized at 19%-20%. 2) Under the impact of the medium, the total content of main amino acids in tobacco leaves showed a downward trend, and the difference of which between the control group and the test group was the most obvious on the fourth day of fermentation. 3) The change trend of the content of petroleum ether extract in cigar leaves for the control group was not obvious, and the content of petroleum ether extract in the tobacco leaves for the test group decreased by 12.4% under the impact of the medium. 4) After fermentation, the relative content of saturated fatty acids for the control group and the test group all increased, while the relative content of unsaturated fatty acids all decreased. 5) After the addition of the medium, the diversity of bacteria on tobacco leaves changed significantly, the number of OTUs in tobacco leaves increased, and the bacterial community structure changed. This research indicates that after adding the medium to ferment cigar filler, the changes of bacterial community and dominant bacterial group on tobacco leaves have impacts on the contents of chemical components in tobacco leaves, and the fermentation with the addition of medium has a positive effect on improving the quality of tobacco leaves.